2015
DOI: 10.1016/j.msec.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic differentiation of human mesenchymal stem cells in freeze-gelled chitosan/nano β-tricalcium phosphate porous scaffolds crosslinked with genipin

Abstract: The objective of this work was to investigate material properties and osteogenic differentiation of human mesenchymal stem cells (hMSCs) in genipin (GN) crosslinked chitosan/nano β-tricalcium phosphate (CS/nano β-TCP) scaffolds, and compare the results with tripolyphosphate (TPP) crosslinked scaffolds. Porous crosslinked CS/nano β-TCP scaffolds were produced by freeze-gelation using GN (CBG scaffold) and TPP (CBT scaffold) as crosslinkers. The prepared CBT and CBG scaffolds were characterized with respect to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 37 publications
(52 reference statements)
2
34
0
Order By: Relevance
“…These characteristics enable it to provide temporary support in the mineralisation stage, accelerate the regeneration process, and improve the mechanical capability of the target position [81]. Our preliminary data are consistent with the results of Siddiqui et al [82], and we found the mean mass loss of scaffold in the first month was 15.70 ± 1.24%, indicating that the scaffold has good degradation ability. When the degradation rate of the scaffold matches the osteogenesis rate of the new bone, the scaffold can provide adequate temporary support.…”
Section: Discussionsupporting
confidence: 90%
“…These characteristics enable it to provide temporary support in the mineralisation stage, accelerate the regeneration process, and improve the mechanical capability of the target position [81]. Our preliminary data are consistent with the results of Siddiqui et al [82], and we found the mean mass loss of scaffold in the first month was 15.70 ± 1.24%, indicating that the scaffold has good degradation ability. When the degradation rate of the scaffold matches the osteogenesis rate of the new bone, the scaffold can provide adequate temporary support.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies also show that β-TCP promotes hBMSC proliferation and differentiation 39 . The injectable PCL/β-TCP composites tested in this study have been shown to be able to release both calcium ions, perhaps because the surface-mediated Ca ion exchange affects cell behavior.…”
Section: Discussionmentioning
confidence: 56%
“…Cell adhesion is enhanced via surface modifying CS using integrin binding ligands or proteins with Arginine–Glycine–Aspartic acid (RGD) binding sequence . Fibrin is one such protein with plenty of RGD sequences, which when coated on genipin cross‐linked CS/nano β‐tricalcium phosphate composite scaffold displayed higher cell attachment . RGD functionalized CS derivative, carboxymethyl‐trimethyl CS (CM‐TM‐CS), showed a drastic improvement in cell adhesion due to the presence of RGD‐peptides, which facilitated the binding to the cells to attain a well‐spread morphology ( Figure ) .…”
Section: Surface Modification Of Cs Biocomposites In Btementioning
confidence: 99%